Analisa Perbandingan Kekuatan Material Pada Anchor Bolt Untuk Perbaikan Pondasi Chimney Boiler Takuma N 1000 Kapasitas 35 Ton Uap/Jam - Tanjung, Muhammad Ridho Yullah; Supriadi, Supriadi; Abdilah, Tomi (Rekayasa Material, Manufaktur dan Energi, 2025)
A steam boiler is an energy conversion machine to change water into steam by heating. To produce steam, water is heated by burning fuel in the steam boiler combustion chamber. The process of burning the shells and fibers as fuel for a steam boiler produces smoke so that the fuel combustion process is not disturbed by the smoke and the hot air is channeled into the chimney and comes out as free air. Specifications for chimneys at PT palm oil mills. XYZ is 26 meters high, 2.1 meters in diameter, and made of steel plate. Gradually, the chimney experienced corrosion due to the age of the material, so the author conducted research for preventive maintenance measures without having to dismantle the entire chimney foundation by connecting anchor bolts. This type of research is qualitative experimental research by carrying out tensile strength tests of Steel BJTP280  anchor bolts in the metal laboratory at the University of North Sumatra. The anchor bolt material is steel with a diameter of 21 mm and a length of 404 mm. There are 9 anchor bolt workpiece specimens with the following details: 3 anchor bolts without welding treatment, 3 anchor bolts with welding treatment, and 3 anchor bolts using stiffener. From the results of the tensile test, the strength of the anchor bolt material without welding treatment was obtained with a maximum force of 180 kN with a yield stress of 443.30 Mpa and a strain of 27%. Meanwhile, the anchor bolt material was welded with a maximum force of 175 kN with a yield stress of 331.63 Mpa and a strain of 8.5%. And for anchor bolt material with Stiffener treatment with a maximum force of 183 kN with a yield stress of 336.26 Mpa and a strain of 13.5%. In conclusion, of the 9 test objects carried out by the anchor bolt tensile test, the strongest was the specimen with Stiffener treatment.